Are there differences between male and female badminton athletes in sleep, physical activity and sedentary time? - Santos, Arilene Maria da Silva; Ribeiro, Sérgio Luiz Galan; de Sousa Junior, Antônio Valdeci Marreiro; Machado, Dionis de Castro Dutra; Monteiro, Paula Alves [UNESP]; Moura, Pedro; Martins, Clarice Maria de Lucena; Freitas Junior, Ismael Forte [UNESP]; Dos Santos, Marcos Antônio Pereira; Rossi, Fabrício Eduardo (FapUNIFESP (SciELO), 2021)
Introduction: High-performance athletes often undergo periods of exhaustive training and insufficient recovery, which can lead to decreased performance, but it is not clear whether there are any differences between the sexes in the level of habitual physical activity, sedentary time or sleep quantity and quality in young highly trained badminton athletes. Objectives: The aim of this study was to compare the habitual physical activity (PA), sedentary time and sleep quantity and quality of highly trained young male and female badminton athletes and non-athletes. Methods: Twenty-seven young badminton athletes and twenty-one non-athletes (control group) were recruited. Sleep duration and quality (total time in bed, total sleep time, wake after sleep onset, sleep efficiency and latency), total counts, vigorous activity time and sedentary time were measured using a tri-axial accelerometer. Results: Male athletes spent less sedentary time (p=0.028), more time in vigorous activity (p=0.016) and had higher total counts (p<0.001) than the male control group. There were no significant differences in sedentary time (p=0.702) or vigorous activity time (p=0.205) between the female athletes and non-athletes, but the female athletes accumulated higher total counts than the female control group (p=0.003). There were no significant differences between the sexes or groups for time in bed, total sleep time, sleep efficiency, wake after sleep onset and latency (p> 0.05). Conclusion: Among males but not females, young highly trained badminton athletes had less sedentary time and more time in vigorous activity than the non-athletes, however, there were no significant differences between the sexes or groups in sleep quantity and quality. Level of evidence III; Case-control study.
¿existen diferencias entre atletas de basdminton masculinos y femeninos en el sueño, actividad física y tiempo de sedentarismo?
Existem diferenças entre atletas de badminton masculinos e femininos no sono, atividade física e tempo de sedentarismo?
Keywords: Athletes; Physical activity; Racquet sports